Pengelolaan Kampung Nelayan Sebagai Desa Wisata di Kabupaten Majene, Sulawesi Barat - Ilham Junaid; Maryam Yusuf; Nur Salam; Muh. Arfin M. Salim; Andi Nur Fauziah (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2020)
This research aims at 1) analyzing the tourism potential of Kampung Nelayan (Majene Regency) as tourism village; 2) recommending steps or mechanisms to implement Kampung Nelayan as tourism village. This paper employs a qualitative approach to answer research questions through research visit in July and September 2019. The authors collected research data through in-depth interviews and direct observation. The research reveals that Kampung Nelayan has the potential for tourism village based on community empowerment principles. Kampung Nelayan has potential of marine tourism and cultural tourism. The steps to implement Kampung Nelayan as tourism village including 1) identification of members of community under the categories of internal and external community groups; 2) involving the community members in tourism programs and 3) follow up of community collaboration by the internal and external groups of community.